The Cleveland Clinic Foundation intensive review of internal medicine - Stoller, James K.; Michota, Franklin A.; Mandell, Brian F. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
Offers thorough preparation for board certification and recertification exams in internal medicine. Clinical vignettes and bulleted lists throughout the book highlight key clinical points. This edition also includes boxed "Points to Remember". Board simulations appear at the end of each section. An updated mock board exam containing over 200 multiple-choice questions appears at the end of the book.